Electrical conductivity studies of anatase TiO2 with dominant highly reactive {0 0 1} facets - Pomoni, K.; Sofianos, Veronica; Georgakopoulos, T.; Boukos, N.; Trapalis, C. (Elsevier B.V., 2013)
Nanostructured powders of titanium dioxide anatase nanoplates with dominant highly reactive {0 0 1} facets were fabricated using a solvothermal method. Two kinds of samples, as prepared and calcinated at 600 °C, were studied using X-ray diffraction (XRD), transmission electron microscopy (TEM), and electrical conductivity in vacuum and in air. The dependence of the conductivity versus the inverse of temperature in the temperature range 150-440 K indicated the contribution of at least two conduction mechanisms in vacuum. The electron transport was controlled by partially depleted of charge carriers grains and adiabatic small polaron conduction in the high temperature regime and by Mott variable-range hopping (VRH) at lower temperatures. The environment was found from the experimental results to influence significantly the electrical conductivity values and its temperature dependence. A decrease with temperature in air is observed in the ranges 290-370 and 285-330 K for the as prepared and the calcinated sample respectively. Potential barriers caused by partial depletion of carriers at grain boundaries control the electrical conductivity behavior in air at high temperatures and VRH in the lower temperature regime.